2020
DOI: 10.1111/jcpp.13259
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and environmental influences on the developmental trajectory of callous‐unemotional traits from childhood to adolescence

Abstract: Background: This study examined the genetic and environmental influences underlying baseline level and developmental course of callous-unemotional (CU) traits across childhood and adolescence. Methods: The data on 8,958 twin pairs (3,108 MZ twin pairs and 5,850 DZ twin pairs) from the Twins Early Development Study were analysed. CU traits were assessed at ages 7, 9, 12 and 16 by mothers and analysed using a biometric latent growth model. Results: Individual differences in the baseline level of CU traits were h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 46 publications
1
17
0
Order By: Relevance
“…The 52 studies included in the review identified CU traits in samples of youth with different behavioral (ODD, CD) or neurodevelopmental disorders (ADHD, ASD). Sample sizes differed significantly among studies (N = 23 in the study of Kimonis [ 87 ] to N = 8958 in the study of Takahashi [ 88 ]) depending essentially on the study design. One study examined monozygotic twin families [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 52 studies included in the review identified CU traits in samples of youth with different behavioral (ODD, CD) or neurodevelopmental disorders (ADHD, ASD). Sample sizes differed significantly among studies (N = 23 in the study of Kimonis [ 87 ] to N = 8958 in the study of Takahashi [ 88 ]) depending essentially on the study design. One study examined monozygotic twin families [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…To assess psychopathic tendencies in youth, studies also used the Antisocial Process Screening Device (APSD) [ 89 ], in particular the callous-unemotional subscale, e.g., [ 88 ] and the narcissism and impulsivity subscales, e.g., [ 88 ], the Youth Psychopathic Traits Inventory (YPI; [ 90 ]), or the Childhood Psychopathy Scale (CPS, [ 91 ]). One study also used some items of the Strength and Difficulties Questionnaire (SDQ; Goodman, 1997) to assess CU traits [ 88 ], and another used the Preschool Forms of the Achenbach System of Empirically Based Assessment (ASEBA, [ 92 ]) to assess early CU behaviors. Finally, Crum et al [ 70 ] used the CU subscale of the Nova Scotia Modified IOWA Conners (NSIC; [ 93 ]) as the ICU or the APSD were not published at the time of research [ 70 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The paper by Takahashi, Pingault, and Viding (2020) addresses a critically important topic, uses exemplary methodology, and is written very clearly with a masterful grasp of the subject area. As noted by Takahashi et al, there has been substantial research (including work by these authors using this same large twin data set) documenting the strong genetic influence on both CU traits themselves, as well as on the conduct problems displayed by these children.…”
Section: But What Genes?mentioning
confidence: 99%
“…© 2020 Association for Child and Adolescent Mental Health. doi:10.1111/jcpp.13291Commentary onTakahashi et al (2020) …”
mentioning
confidence: 99%